2014
DOI: 10.3174/ajnr.a3998
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Volume in the Deep Gray Matter: Association with Cognitive Impairment in Multiple Sclerosis

Abstract: BACKGROUND AND PURPOSE:There is a well-established correlation between deep gray matter atrophy and cognitive dysfunction in MS. However, the cause of these signs of neurodegeneration is poorly understood. Iron accumulation in the deep gray matter is higher in patients with MS compared with age-and sex-matched healthy controls, and could contribute to disease progression. Our objective was to evaluate the relationship between iron and cognition in several deep gray matter structures while accounting for the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
28
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 37 publications
(43 reference statements)
4
28
1
1
Order By: Relevance
“…However, after they adjusted for regional volumes, iron-cognition links were no longer significant. Thus, unlike in the current study using QSM and R2*, Modica et al 8 found no relationship between their iron measure and cognition when regional atrophy was controlled. Pinter et al 10 reported correlations between a processing speed ("cognitive efficiency") composite score (SDMT, PASAT) and a combined basal ganglia R2* measure, while controlling for global brain measures (normalized brain volume, lesion load, magnetization transfer ratio for normal-appearing brain tissue).…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…However, after they adjusted for regional volumes, iron-cognition links were no longer significant. Thus, unlike in the current study using QSM and R2*, Modica et al 8 found no relationship between their iron measure and cognition when regional atrophy was controlled. Pinter et al 10 reported correlations between a processing speed ("cognitive efficiency") composite score (SDMT, PASAT) and a combined basal ganglia R2* measure, while controlling for global brain measures (normalized brain volume, lesion load, magnetization transfer ratio for normal-appearing brain tissue).…”
Section: Discussioncontrasting
confidence: 90%
“…Our findings extend the limited literature on relationships between DGM iron and cognition in MS. Only 2 previous studies concurrently accounted for regional 8 or global atrophy 10 and reported, similarly, moderate relationships between DGM iron and cognition. Modica et al 8 used susceptibility-weighted imaging to assess DGM iron.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…6,7 On the contrary, other MR imaging studies with R2*, QSM, magnetic field correlation imaging, or phase imaging showed no significant difference 1,36 or even higher iron concentration in the thalamus in patients with RRMS. 2,8,37,38 The cause of these contradictory findings is not clear. Because the disease duration of the RRMS group included in our study was rather long compared with other studies and thalamic iron content was negatively correlated with EDSS, one can speculate that iron may accumulate in the early MS stage, while its concentration may decrease in the later stage of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…in clinically isolated syndrome [35,156,157]. Iron concentration in the basal ganglia, mostly in the putamen and caudate nucleus was associated with increased disability and cognitive dysfunction [34,158,159]. In MS plaques, increased iron concentration either in the peripheral rim or diffusely within the lesion has been documented in the subacute stage of the lesion evolution.…”
Section: Multiple Sclerosismentioning
confidence: 99%